FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI PERAWAT UNTUK MELANJUTKAN PENDIDIKAN PADA JENJANG PENDIDIKAN TINGGI KEPERAWATAN - Dony Setiawan Hendica Putra (Jurnal Kesehatan dr. Soebandi, 2014)
Advances in science and technology in the field of nursing, as well as the demands of society to obtain quality health services are also increasing. But the reality in the field of nursing staff with S1 / Bachelor of Nursing qualifications up to the year 2008 in Kalisat Hospital Jember as many as 2 people. This is allegedly due to the lack of motivation of nurses to continue their education to a higher level. For this reason, researchers identify the motivation of nurses to continue their education through the Nursing Undergraduate level, as well as identifying factors related to that motivation. The research design used was analytic cross sectional. The total sample used was 58 people using purposive sampling technique. Data analysis uses Linear Regression test calculations with a significance level of ρ <0.05. The results showed that the motivation of most of the IRNA nurses at Kalisat Hospital was relatively high to continue their education (67%). There is a relationship between age and motivation with a value of ρ = 0,000 (ρ <0.050), there is a gender relationship with a motivation of significance value ρ = 0.021 (ρ <0.050), there is a relationship between marital status and motivation with a value of ρ = 0.011 (ρ <0.050 ) and there is no relationship between superiors' support and motivation to continue their education to a higher level ρ = 0.372 (ρ> 0.050). The dominant factor that affects is the age factor